Biochemical analysis of anti-pathogenic bacteria activity of bioactive components from Sclerocarya birrea stem bark via experimental and in-silico approaches - Ufelli, Balogun Sadiya; Abisoye, Larayetan Rotimi; Abioye, Oluwatayo Emmanuel; Oyebamiji, Abel Kolawole; Gideon, Ayeni; Joshua, Balogun; Abdulraraq, Yahaya (Eclética Química, 2026)
In this study, two compounds derived from the bioactive components of Sclerocarya birrea (S. birrea), a plant native to Nigeria, were examined for their biochemical composition, antibacterial effectiveness, and molecular structure. Pyrogallol (94.72 and 46.77%) and hydroxyquinol, which was exclusively identified in the hexane extract, were the main bioactive components extracted from the study plant S. birrea (52.71%). A polyphenolic chemical known as pyrogallol has been shown to have extensive antibacterial activity. The ethanol and hexane bark extracts from S. birrea demonstrated significant antibacterial potential against the entire panel of bacteria tested in this study, indicating that the plant's extracts have a wide range of activity compared to the bacteria of interest most frequently responsible for urinary tract infections. Due to the high phenolic concentration in the plant's bark extract, the antiradical results also showed that S. birrea had a very significant antioxidant capacity. It was found from the molecular docking that pyrogallol could inhibit 80% of the studied receptors.